The potential of regulating ecosystem service – filtering potential for inorganic pollutants – supplied by soils of Slovakia - Makovníková, Jarmila; Pálka, Boris; Širáň Miloš; Kizeková, Miroslava; Kanianska, Radoslava (Hungarian Geographical Bulletin, 2019)
The concept of agroecosystem services combines environmental and socio-economic approaches to the analysis and evaluation of natural capital. A multi-criteria approach to spatial quantification of ecosystem services allows explicit assessment of the potential of agroecosystems to provide agroecosystem services and to adapt the land management under regional conditions. For the spatial quantifying of agroecosystem services potential of agricultural land in Slovakia, we have created a mapping unit by combining four input layers (climatic region, slope topography, soil texture and land use). In ecosystems of agricultural land, regulation of water regime, control of soil erosion, climate regulation and soil filtration are the main regulating services. Filtering potential was calculated as accumulative function of soil sorption potential and potential of total content of inorganic pollutants evaluated according to The Slovak Soil Law. Calculated potential was categorised into five categories (very low, low, medium, high and very high). The distribution of the filtering potential using spatial mapping units show that in Slovakia more than 41 per cent of agroecosystems have very high filtering potential (for inorganic pollutants), mostly in the Bratislava, Nitra and Trnava regions. Ecosystems with low potential (more than 41 per cent of agricultural land) are predominantly located on Fluvisols (along Váh, Hron and Bodrog rivers) with a higher content of risk elements in alluvial sediments (caused by anthropogenic deposition). The mountain soils on grassland are also strongly involved in very low category of filtering potential, predominantly in the Banská Bystrica, Žilina and Prešov regions. The greatest differences among regions was found in relation to climatic conditions, land use and the diversity of soil types.